What Is Unique about the New Canadian COPD Guidelines? - Denis E O'Donnell (Canadian Respiratory Journal)
The prospect of digesting yet another set of ?best practice? guidelines is not an appealing one for the overwrought family physician. The Canadian Thoracic Society (CTS) panel, charged with the enormous task of developing new evidencebased recommendations, was acutely aware of this. Nevertheless, they were convinced that the time was right to tackle this important educational initiative, and somehow managed to summon considerable reserves of energy and enthusiasm to produce an excellent, state-of-the-art compendium on the optimal management of this condition (1). Faced with the evidence that death rates from chronic obstructive pulmonary disease (COPD) continue to escalate in Canada and that its prevalence has risen to unprecedented levels (particularly in older women), the panel believed that there was an urgent need to raise awareness of this disease, and to optimize diagnosis and management (2).